Revisiting curriculum design in architectural education in Nigeria: the information technology factor. (2012)
Architectural education has had a chequered history of half a Century in Nigeria. The British bequeathed the curriculum of architectural training, as indeed the entire Nigerian educational system. The architecture programmers in Nigerian Schools of architecture, though fashioned after the British and/or American model, are tailored to meet the nation’s socio-economic needs and cultural values within the general context of the Nigerian Nations; Policy on Education. The adequacy of the curriculum in responding to the. changing technological and socio-economic situation of She country and global trends has suggested continual appraisal in recent times. The advances in technology, especially information technology, have mads a re-direction in architectural education in Nigeria imperative. This paper critically appraises this development as the use of the computer has made tremendous inroads into architectural practice in the country. JS reports findings on the authors’ research on the influence of Computer-Aided’ Design (CAD) on architectural practice in Nigeria, shelving that only 30% of practicing architects began So us® -CAD software during their course of architecture!-study. It asserts that the absence of,- or inadequate CAD training in schools of Architecture in Nigeria, has significantly affected the. performance off architects in practice. The paper proffers recommendations on curriculum ' re-design to meet the challenges of information technology, in Nigeria.